Analyzing Project Management Maturity Level in Indonesia - Simangunsong, Eliot; Silva, Elisabeth N. Da (UI Scholars Hub, 2013)
Project management has been generally known and increasingly used by many organizations to gain competitive advantage. In this context, many studies have proposed maturity models to evaluate how project management knowledge has been deployed effectively and efficiently in organization. As a developing country, Indonesia needs many development projects managed by government and private companies in different industries. Here, a study to assess project management maturity level in Indonesian businesses may bring insight about current business practices, which is important to speed up country development and business sustainability. Adapting the Project Management Maturity Model (ProMMM), a survey instrument has been developed and applied to professionals from Jakarta and surrounding area. The result of analysis shows that construction and primary industry have a higher maturity level compare to manufacturing and services. It is to be noted, however, that the level of project management understanding is low across industries. This indicates that more quality project management training or certification is required to improve overall project management knowledge in Indonesia.